Novel Materials From the Supramolecular Self-Assembly of Short Helical β3-Peptide Foldamers - Kulkarni, Ketav; Habila, Nathan; Del Borgo, Mark P.; Aguilar, Marie-Isabel (Frontiers in Chemistry, 2019)
Self-assembly is the spontaneous organization of small components into higher-order structures facilitated by the collective balance of non-covalent interactions. Peptide-based self-assembly systems exploit the ability of peptides to adopt distinct secondary structures and have been used to produce a range of well-defined nanostructures, such as nanotubes, nanofibres, nanoribbons, nanospheres, nanotapes, and nanorods. While most of these systems involve self-assembly of α-peptides, more recently β-peptides have also been reported to undergo supramolecular self-assembly, and have been used to produce materials—such as hydrogels—that are tailored for applications in tissue engineering, cell culture and drug delivery. This review provides an overview of self-assembled peptide nanostructures obtained via the supramolecular self-assembly of short β-peptide foldamers with a specific focus on N-acetyl-β3-peptides and their applications as bio- and nanomaterials.